Ex vivo AKT-inhibition facilitates generation of polyfunctional stem cell memory-like CD8+ T cells for adoptive immunotherapy - Mousset, Charlotte M.; Hobo, Willemijn; Ji, Yun; Fredrix, Hanny; De Giorgi, Valeria; Allison, Robert D.; Kester, Michel G. D.; Falkenburg, J. H. Frederik; Schaap, Nicolaas P. M.; Jansen, Joop H.; Gattinoni, Luca; Dolstra, Harry; et al. (OncoImmunology, 2018)
Adoptive T cell therapy has shown clinical potential for patients with cancer, though effective treatment is dependent on longevity and potency of the exploited tumor-reactive T cells. Previously, we showed that ex vivo inhibition of AKT using the research compound Akt-inhibitor VIII retained differentiation and improved functionality of minor histocompatibility antigen (MiHA)-specific CD8+ T cells. Here, we compared a panel of clinically applicable AKT-inhibitors with an allosteric or adenosine triphosphate-competitive mode of action. We analyzed phenotype, functionality, metabolism and transcriptome of AKT-inhibited CD8+ T cells using different T cell activation models. Most inhibitors facilitated T cell expansion while preserving an early memory phenotype, reflected by maintenance of CD62L, CCR7 and CXCR4 expression. Moreover, transcriptome profiling revealed that AKT-inhibited CD8+ T cells clustered closely to naturally occurring stem cell-memory CD8+ T cells, while control T cells resembled effector-memory T cells. Interestingly, AKT-inhibited CD8+ T cells showed enrichment of hypoxia-associated genes, which was consistent with enhanced glycolytic function. Notably, AKT-inhibition during MiHA-specific CD8+ T cell priming uncoupled preservation of early memory differentiation from ex vivo expansion. Furthermore, AKT-inhibited MiHA-specific CD8+ T cells showed increased polyfunctionality with co-secretion of IFN-γ and IL-2 upon antigen recall. Together, these data demonstrate that AKT-inhibitors with different modality of action promote the ex vivo generation of stem cell memory-like CD8+ T cells with a unique metabolic profile and retained polyfunctionality. Akt-inhibitor VIII and GDC-0068 outperformed other inhibitors, and are therefore promising candidates for ex vivo generation of superior tumor-reactive T cells for adoptive immunotherapy in cancer patients.
CRIS-Team Scopus Importer:2023-03-23
Keywords: adoptive transfer; AKT; CD8; glycolysis; polyfunctionality; stem cell memory